The journey of Malaysian NCVD-PCI (National Cardiovascular Disease Database-Percutaneous Coronary Intervention) Registry: A summary of three years report - Ahmad, W.A.; Ali, R.M.; Khanom, M.; Han, C.K.; Bang, L.H.; Yip, A.F.; Ghazi, A.M.; Ismail, O.; Zambahari, R.; Hian, S.K. (Elsevier, 2011)
INTRODUCTION: The Malaysian National Cardiovascular Disease Database (NCVD) team presents Percutaneous Coronary Intervention (PCI) Registry report for the year 2007 to 2009. It provides comprehensive information regarding practice and outcome of PCI in Malaysia.